Integration of geoinformation with geological and geophysical approaches for potential groundwater exploration - Zamari, Muhamad Asyraf (2022)
Groundwater is one of the most important water source alternatives to meet daily needs especially for a clean drinking water supply. However, the major concern in groundwater exploration is to determine the precise location of the groundwater source zone. This study aimed to integrate the geoinformation approaches into the potential area of groundwater exploration area at Universiti Teknologi Malaysia (UTM), Johor. Aerial images were captured using a photogrammetry approach incorporated with precise Global Positioning System (GPS) ground control points to generate topographic map for the study area, which form as the primary data source. It was found that the positional accuracy of the horizontal and vertical components for this topographic information was 9.1 cm and 10.3 cm respectively, at 95% confidence level. Meanwhile, the secondary data source consists of geological and geophysical data. Existing geological maps were extracted, and the rock samples were collected through field geological investigations. After that, two types of geophysical data collection were implemented in the study area, namely resistivity and seismic refraction with four resistivity lines (R1-R4) and one seismic line (S1). Then, the subsurface geological information such as lithology and geological structure were combined together to evaluate the subsurface profile. The subsurface profile model indicated that the zone of low resistivity with a value <300 Ohm m was identified on the resistivity lines R2 and R3, and it was interpreted as a saturated zone that has potential as a source of groundwater. The geospatial database was developed with the used of Geographic Information System (GIS) software. A map of the potential groundwater zone was generated and two potential locations of groundwater resources, namely A1 and A2, have been identified based on the line of resistivity R2 with coordinate location is -52364.90 m E, 7748.82 m N and -52376.90 m E, 7806.70 m N, respectively. Finally, locations of these groundwater resources were marked on the ground by using the GPS real-time kinematic (RTK) method. The drilling process has discovered the groundwater source in gabbro rock aquifers with a final depth of 158 m and preliminary estimate of the groundwater rate was found more than 0.5 million of litres per day. Based on the success of the discovery of groundwater resources in the study area, it has been proven that integrating geoinformation approaches has a significant impact on groundwater exploration work.